2022
DOI: 10.1155/2022/5467712
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Warm Needle Acupuncture plus Xitong Waixi Lotion in Patients with Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Objective. To evaluate the effect of warm needle acupuncture plus Xitong Waixi lotion on the levels of IL-1, TNF-α, and MMP-3 in patients with knee osteoarthritis. Methods. Eighty patients with knee osteoarthritis admitted to our hospital from October 2019 to June 2021 were recruited and assigned via the random number table method at a ratio of 1 : 1 to receive either Xitong Waixi lotion (conventional group) or warm needle acupuncture plus Xitong Waixi lotion (combined group). Outcome measures included clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is found that this combination therapy with addition of Modified Danggui Sini Decoction could achieve good results in the treatment of KOA, significantly reducing the symptoms of knee pain and swelling, and improving the function of the knee joint [10]. Sheng Guangyun used a randomized number table to divide the 80 patients into a conventional group, which received Xitong Waixi lotion treatment, and a combined group, which was treated with warm acupuncture on top of the former and found that the clinical efficacy of the combined group was significantly improved after treatment (p=0.006) [11].…”
Section: Combined Use Of Warm Acupuncture and Chinese Medicinementioning
confidence: 99%
“…It is found that this combination therapy with addition of Modified Danggui Sini Decoction could achieve good results in the treatment of KOA, significantly reducing the symptoms of knee pain and swelling, and improving the function of the knee joint [10]. Sheng Guangyun used a randomized number table to divide the 80 patients into a conventional group, which received Xitong Waixi lotion treatment, and a combined group, which was treated with warm acupuncture on top of the former and found that the clinical efficacy of the combined group was significantly improved after treatment (p=0.006) [11].…”
Section: Combined Use Of Warm Acupuncture and Chinese Medicinementioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%